Effects of bilingual and peer-tutoring instructional strategies on pre-service teachers’ achievement in Yoruba translation (2013)
Translation is an important aspect of Yoruba language studies and a compulsory course for pre-service teachers in colleges of education. As valuable as it is, reports show that there is a gross underachievement in it among students. This has been traced to ineffective strategies adopted in teaching translation to pre-service teachers which do not allow them to be actively involved in the teaching learning process. There is the need to adopt strategies that cater for these deficiencies. Two of such strategies are bilingual and peer- tutoring. Studies have shown that these strategies were effective in teaching social studies and mathematics but their effect in teaching and learning of Yoruba translation has not enjoyed much research attention. This study examined the effects of bilingual and peer- tutoring instructional strategies on pre-service teachers' achievement in Yoruba translation. Pretest-posttest control group quasi- experimental research design was adopted. 300 pre-service teachers in intact classes from six purposively selected colleges of education in southwestern Nigeria were randomly assigned to treatment groups. Yoruba Translation Achievement Test (r = 0. 73) and Instructional Guides for the three strategies were the instruments used. Seven null hypotheses were tested at 0.05 significant level. Data were analysed using Analysis of Covariance and Scheffe post- hoc analysis. Bilingual and peer-tutoring instructional strategies are more facilitative in fostering pre-service teachers' accurate translation in Yoruba than the traditional lecture strategy. Hence, Yoruba translation teachers in colleges of education should adopt the strategies in Yoruba translation